Quality of life in individuals initiating antiretroviral therapy: a cohort study - Pimentel, Gabriela Sales; Ceccato, Maria das Graças Braga; Costa, Juliana de Oliveira; Mendes, Jullye Campos; Bonolo, Palmira de Fátima; Silveira, Micheline Rosa (Revista de Saúde Pública, 2020)
OBJECTIVE: To assess longitudinally the change in quality of life in people living with HIV initiating antiretroviral therapy in three public reference services specialized in HIV care in Belo Horizonte, Brazil. METHODS: Prospective cohort study among people living with HIV, aged 18 years or older, and initiating antiretroviral therapy. We obtained sociodemographic, behavioral, clinical data related to pharmacological treatment and to the service by face-to-face interviews, and supplemented these data with information from clinical records and Information Systems of the Brazilian HIV/AIDS Program. We measured the quality of life using the WHOQOL-HIV bref instrument, with a minimum interval of six months between the baseline and the follow-up interviews. We used paired t-test to assess the mean change in quality of life between the two interviewsand evaluated factors associated with this outcome using multiple linear regression. RESULTS: The overall quality of life, as well as the physical, psychological, level of independence, environment and spiritual quality of life domains were statistically higher in people living with HIV using antiretroviral therapy at the end of the follow-up. Factors independently associated with the increase in quality of life were having religious belief and living with other people. Having signs or symptoms of anxiety and depression and the number of adverse drug reactions reported were predictors associated with worsening quality of life. CONCLUSIONS: These results show an improvement in the quality of life over time in people living with HIV on antiretroviral therapy. They also highlight the need to monitor and provide health care support, especially for individuals with signs and symptoms of anxiety and depression and that report adverse reactions to medicines at the beginning of treatment.